Le dimorphisme sexuel de conformation de l’os coxal humain. Bases biologiques et nouvelles applications possibles - François Marchal (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The extent of sexual dimorphism of the human hip bone is a characteristic widely exploited in sex diagnosis of the skeleton. A morphometrical analysis based on the concepts of mathematical morphology allows clear attribution of the areas of the pelvic bone which present the greatest dimorphism in shape. These are the ilium in its entirety, the sacral plane and the pubis. The pubis is already very widely used in techniques of sexual diagnosis. It should be possible to develop and test new approaches which deal more with the conformational dimorphism of the ilium and its posterior part. This would be an advantage in the case of fragmentary pelvic bones and could possibly be used for assessing the sex of pelvic remains of non-modern fossil Homo.